Contributions of Africana Scholars to the Theory of Human Rights in Sociology - Agozino, Biko (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2014)
Eurocentrism dominates and distorts human rights discourse as is the case with almost every other topic in sociology. The assumption is that human rights are Western values with the best exemplars of the tradition to be found in western liberal democratic states based on theoretical and legal-philosophical ideas developed by the Enlightenment and by the Western scholars who inherited that tradition. By neglecting other communities of interpretation on the human rights discourse, Eurocentrism contributes to the stunting of social thought the way ethnocentrism usually does. This papyrus departs from the Eurocentric approach by focusing on the profound contributions of people of African descent to the theoretical clarification of human rights issues and to the heroic historical struggles to advance the practice of human rights for all of humanity.